Pengaruh Pertumbuhan Laba, Suku Bunga, Payout Ratio dan PE t-1 Ratio Terhadap Harga Saham/Earning - Maulana, Dede Yusuf; Nusannas, Iman Sidik; Amruloh, Dedeng Abdul Gani (Eqien - Jurnal Ekonomi dan Bisnis, 2024)
Stock are securities that are signs of a person or entity ownership of a company. In certain market conditions the stock price can be undervalued or overvalued in which both can be analysed by using stock valuation models. The purpose of this study is to test some of the stock price valuation models on the shipping company listed on the Indonesian Stock Exchange. The are is PE. The analysing conducted by multiple regression to the sample companies listed on the Indonesia Stock Exchange during 2019-2023, at shipping company. P/E model variable payout Ratio and P/Et-1 a positif significant influence on the P/E, while the Growth and Beta have no effect on the P/E. PE model have the R Squared of 22,22%.